Messing around In the Iraqi theatrical text (Journal of the College of Basic Education, 2022)
Each stage in the history of theater and theatrical literature, since its inception during the days of the ancient Greeks until today, has its customs and traditions that the path followed according to the needs of society and artistic necessities, and each play had its form and content according to customs and traditions. Aristotle was the first to He looked at the components of tragedy and comedy, their origins, form, and construction, and the playwrights applied them in their writings.When the playwrights felt, after a period of time